Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Operasi Bilangan Bulat - Faridiana, Faridiana; Rismawati, Rismawati (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
The purpose of this research is to determine students' difficulties in solving integer operation problems at SMP Negeri 3 Kuala Batee. The type of research used in this research is descriptive qualitative with test and interview data collection techniques. The subjects used in this research were 11 students in class VII of SMP Negeri 3 Kuala Batee. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results that can be obtained in research on students' analytical difficulties in solving integer operation problems are 1) students have difficulty in understanding the basic concept of integers, 2) students have difficulty in mixed operations (division, multiplication,addition, subtraction) 3) difficulty in understanding the meaning in story problems and writing the language in story problems into mathematical.